IMPLEMENTATION OF DIGITAL MARKETING ON SMALL AND MEDIUM ENTERPRISES - Rini Hakimi; Widya Fitriana; Rika Hariance (Socio-Economics/Agribusiness Department, 2023)
Information and communication technology advancement can transform traditional marketing into internet-based marketing. Marketing digitalization was initially more researched in large companies but was still limited in digital marketing research in SMEs. This study aims to close a knowledge gap to describe the implementation of digital marketing in SMEs and analyze the impact on SME performance. This study used 184 samples of SMEs in West Sumatra. Research variables include entrepreneur aspects, business aspects and infrastructure aspects. The data were analyzed using descriptive and binary logits. The findings show that gender and firm size significantly influence how well digital marketing is used in SMEs. Women entrepreneurs more intensively use social media for digital marketing activities, but limited resources and infrastructure cause SMEs more limited opportunities to adopt digital marketing.